Variant-dependent oxidative and cytokine responses of human neutrophils to SARS-CoV-2 spike protein and anti-spike IgG1 antibodies - Almeida, Nathalie Bonatti Franco; Fantone, Kayla Marie; Sarr, Demba; Ashtiwi, Nuha Milad; Channell, Sarah; Grenfell, Rafaella Fortini Queiroz; Martins-Filho, Olindo Assis; Rada, Balázs (Frontiers in Immunology, 2023)
Severe forms of COVID-19, the disease caused by SARS-CoV-2, are characterized by acute respiratory distress syndrome, robust lung inflammation and death in some patients. Strong evidence has been accumulating that polymorphonuclear neutrophilic granulocytes (PMN) play an important role in the pathophysiology of severe COVID-19. SARS-CoV-2 directly induces in vitro PMN activation, mainly the release of neutrophil extracellular traps (NETs). However, the viral components inducing this PMN response remain unclear. Here we show that the SARS-CoV-2 Omicron variant spike (S) protein and anti-spike IgG1, either alone or together, stimulate the production of reactive oxygen species (ROS) in human PMNs. We also observed that the SARS-CoV-2 Wuhan S protein and an anti-S IgG1 antibody together trigger myeloperoxidase release from PMNs. Based on the relevance of SARS-CoV-2 and influenza co-infections, we have also investigated the impact of influenza virus infection on the previous PMN responses to S proteins or anti-S antibodies. We did not detect any significant effect of influenza co-infection on ROS generation in PMNs. Our data also show that PMN stimulation by S proteins induced the release of different chemokines, growth factors, regulatory and proinflammatory cytokines. Overall, our findings show that the SARS-CoV-2 S protein, an anti-spike IgG1 antibody or their immune complex, promote oxidative responses of PMNs in a variant-dependent manner, contributing to a better understanding of the role of PMN responses during SARS-CoV-2 infection.